Community College Faculty Self-Efficacy in Student Centered Teaching - Sarah Jane Fishback; Barry B. Leslie; Laura C. Peck; Pamela M. Dietz (Adult Education Research Conference, 2015)
The purpose of this study was to investigate if faculty self-efficacy beliefs impacted their choice of teaching methods in the classroom. Self-efficacy beliefs help to explain teacher instructional activities and their orientation toward the education process. Findings have implications for higher education as the strategies faculty use in the classroom are linked to student success.
Keywords: faculty; community college; self-efficacy; student-centered teaching